2011
DOI: 10.4028/www.scientific.net/amr.188.441
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Drilling Printed Circuit Boards

Abstract: Drilling is a particularly complicated machining process, and it becomes much more complicated when the workpiece is printed circuit boards (PCBs). PCB is composite materials with anisotropy. Even a small defect in PCB may cause great losses. Both the drilling process and PCB structure design have been researched by many scholars. But the investigations into the drilling processes of PCB are not systematic. The present review article address the report about tool materials and geometrics, cutting force, cuttin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Zheng et al. [67] reviewed micro drilling in PCB industries, including tool materials and geometries, thrust force and torque, damage and breakage of micro drilling. They mentioned several micro drilling techniques such as EDM, vibration and laser drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al. [67] reviewed micro drilling in PCB industries, including tool materials and geometries, thrust force and torque, damage and breakage of micro drilling. They mentioned several micro drilling techniques such as EDM, vibration and laser drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al (in press) studied the cutting force of drilling PCB micro holes. Zheng et al (2011b) performed a complete review of drilling PCBs. In this study, several experiments have been performed to study the wear mechanism of micro-drills.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2011), Yang (2011) studied chip morphology when drilling a 3.2-mm hole in RPCs and found that the chips from the resin/glass fiber cloth layer were continuous chips with five different morphologies. Zheng et al (2012a, 2015, 2012b, 2011) studied the drilling characteristics, drilling force, drilling temperature, tool wear mechanism and hole quality optimization of RPCs. Tang (2012), Tang et al (2011a, 2011b) studied the drilling dynamic performance of the drilling system and presented a simulation of ultra-high-speed drilling of the copper foil layer of PCBs using the finite element method.…”
Section: Introductionmentioning
confidence: 99%